2019
DOI: 10.2106/jbjs.18.00326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Image-Derived Instrumentation on Total Knee Arthroplasty Revision Rates

Abstract: Background: Computer navigation and image-derived instrumentation (IDI) are technology-based methods developed to improve outcomes and potentially reduce revision total knee arthroplasty (TKA). IDI refers to the use of manufactured, patient-specific surgical jigs. Conflicting reports exist on IDI-associated improvements in outcomes. The primary aim of the current study was to compare the rates of revision among TKA cases in which components were initially implanted with use of IDI, computer navigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This may be a result of surgeons looking at ways of improving the longevity of TKA implants in younger patients by improving component alignment using technology [9, 15, 31]. There is some evidence that technology‐assisted TKA may be most beneficial for individuals younger than age 65 [14, 33, 43], but this is still a highly debatable topic, and long‐term follow‐up is needed [18, 25].…”
Section: Discussionmentioning
confidence: 99%
“…This may be a result of surgeons looking at ways of improving the longevity of TKA implants in younger patients by improving component alignment using technology [9, 15, 31]. There is some evidence that technology‐assisted TKA may be most beneficial for individuals younger than age 65 [14, 33, 43], but this is still a highly debatable topic, and long‐term follow‐up is needed [18, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Our specialty's reaction has been otherwise. Despite the fact that no welldesigned study about a new implantalignment tool, navigation system, or surgical robot has been shown to improve patient-reported outcomes or implant durability, and despite the fact that the best studies on those innovationsincluding systematic reviews, network meta-analyses, registry reports, and long-term follow-up studies of randomized trials-have found no differences that a patient might perceive [1,2,8,9,13], the use of expensive, unproven technology in our specialty is growing fast. The global use of robotic-assisted knee arthroplasty, for example, will reach approximately 700,000 procedures per year by 2030, sustaining a compound annual growth rate of 8% from 2021 to 2030 [5].…”
mentioning
confidence: 99%
“…As far as we now know, differences in outcomes scores among generally well-performing implants are negligible or nonexistent [2], the odds of a new implant lasting longer than an existing one is hardly better than a coin toss [3,4], and no well-designed study about a novel implant-alignment tool, ligament-balancing approach, or technology-driven innovation has made a dent in patient-reported outcomes or implant durability. The best such studies-systematic reviews, network metaanalyses, registry reports, and long-term follow-up studies of randomized trials-have found no differences at all that a patient might perceive [5][6][7][8][9].…”
mentioning
confidence: 99%